1996
DOI: 10.1007/bf00212670
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organotin compounds in the foodweb of a shallow freshwater lake in The Netherlands

Abstract: An extensive study on the presence of nine organotin compounds (OTs) in a freshwater foodweb was made, using newly developed analytical procedures in order to obtain insight in accumulation and degradation processes. Tributyltin (TBT), Triphenyltin (TPT) and their degradation products were detected. Zebra mussels, eel, roach, bream, pike, perch, and pike perch and cormorant showed high OT body concentrations. At the lower trophic levels, phenyltin concentrations were higher in benthic species while butyltin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 2 publications
1
42
0
Order By: Relevance
“…The organotin levels found in burbot muscle tissue are lower than those reported in eel and pike muscle tissue from fresh water systems in the Netherlands [5] and Canada [17] respectively, Table 5. Levels in eel liver from The Netherlands range from 13 -1 051 ng Sn/g d.w. of the butyltin species and from 2 -1700 ng Sn/g d.w. of the phenyltin species [5].…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…The organotin levels found in burbot muscle tissue are lower than those reported in eel and pike muscle tissue from fresh water systems in the Netherlands [5] and Canada [17] respectively, Table 5. Levels in eel liver from The Netherlands range from 13 -1 051 ng Sn/g d.w. of the butyltin species and from 2 -1700 ng Sn/g d.w. of the phenyltin species [5].…”
Section: Discussionmentioning
confidence: 49%
“…These results show that other sources of contamination must be taken into account when investigating fresh water systems than those considered important in marine systems. It has been reported that triphenyltin is passed on to benthic organisms primarily via sediments [5] and as burbot is a benthivorous species, this may also contribute to the elevated levels reported.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The presence of organotin compounds and of their degradation products in sea [8][9][10][11][12] in fresh-water bodies 13 and in sediments [14][15][16] has recently attracted much attention also, because of their detrimental effects on aquatic organisms, especially bivalve and gasteropods molluscs, 17 fish and birds. 18 In particular, tributyltin (TBT) compounds are present in antifouling paints as active ingredients and continue to pose a major ecotoxicological threat; 19 apart from imposex and growth-related effects of TBT on molluscs, there are other concerns such as contamination of fish products resulting in contamination of human food. 20,21 As a result of the uptake of these compounds into the human body, TBT has been determined in biological samples, 22,23 including human hair.…”
Section: Introductionmentioning
confidence: 99%